Synthesis of N-(3-picolyl)-based 1,3,2λ5-benzoxazaphosphinamides as potential 11β-HSD1 enzyme inhibitors - Balam, S.K.; Krishnammagari, S.K.; Soora Harinath, J; Sthanikam, S.P.; Chereddy,S.S.; Pasupuleti, V.R.; Yellapu, N.K.; Peddiahgari, V.G.R.; Cirandur, S.R. (Springer Science Media New York, 2015)
Inhibition of 11β-HSD1 enzymatic action is perceived as a potential target for the treatment of metabolic syndromes like cardiovascular diseases, obesity, and diabetes. In an attempt to formulate potential organophosphorus compounds against 11β-HSD1 enzyme inhibition, we report novel 6-bromo-3-(6-methyl-2-pyridyl)-2-alkyl/arylamino-3,4-dihydro-2H-1,3,2λ5-benzoxazaphosphinin-2-ones 22a–22n as good in vitro inhibitors of HEK 293 cell lines. The in vivo acute and sub-acute investigations sustain them as good antidiabetic compounds. The computational docking studies performed on them also supported the binding mode of compounds 22a and 22h with 11β-HSD1 protein. The blood glucose level lowering effect of the target compounds 22a–22n screened on the streptozotocin-induced diabetic rats revealed that the target compounds are potential by antidiabetic when compared to the potency of standard glibenclamide drug. In addition, the calculated QSAR parameters, predicted ADMET properties, evaluated bioactivity properties and toxicity risk studies authorize drug like properties to the synthesized compounds